2011
DOI: 10.2105/ajph.2010.193102
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Assessment of the Health of Homeless Families in New York City, 2001–2003

Abstract: Morbidity and mortality levels were comparable between homeless and low-income adults; homeless children's slightly higher risk on some measures possibly reflects the impact of poverty and poor-quality, unstable housing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 12 publications
0
38
0
Order By: Relevance
“…The one study by Kerker and her colleagues that examines mortality among this major subgroup of the homeless population finds that factors and outcomes related to mortality were very different for adults who were homeless as part of families, to the point that they should be considered separately from adults who were homeless as single adults. These findings, also based upon a NYC shelter population, found their mortality rates to be comparable to other low-income adults, 40 and lower than that of the single adult population. 14 These differential mortality rates underscore other fundamental differences between adults in homeless families and their single adult counterparts.…”
Section: Introductionmentioning
confidence: 50%
“…The one study by Kerker and her colleagues that examines mortality among this major subgroup of the homeless population finds that factors and outcomes related to mortality were very different for adults who were homeless as part of families, to the point that they should be considered separately from adults who were homeless as single adults. These findings, also based upon a NYC shelter population, found their mortality rates to be comparable to other low-income adults, 40 and lower than that of the single adult population. 14 These differential mortality rates underscore other fundamental differences between adults in homeless families and their single adult counterparts.…”
Section: Introductionmentioning
confidence: 50%
“…Studies 3,10,11,16,17,25,27 conducted in several different cities around the world showed that the prevalence of HIV infection among homeless people is signifi cantly higher than in the general population. In the present study, however, this rate was as high as in those population groups most affected by the HIV/AIDS epidemic in Brazil such as sex workers 23 (4.8%) and MSM 13 (13.6%).…”
Section: Discussionmentioning
confidence: 99%
“…It might be consequential to the extreme vulnerability that is inherent to living on the streets, 1,15,28 and such a condition overlaps with other factors typically associated with poverty and social inequality in the general population. In other words, living on the streets and insecurity related to having no housing 7,11,20,28 are per se factors that bring about situations of greater exposure to HIV such as violence and no access to services. 14,26,29 These same particularities may largely explain the study fi nding that young, female and homeless individuals engaging in homosexual sex are more vulnerable to HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) The feeling of not being supported can lead to abandonment of therapy. For this reason, it is necessary to recognize and consider social, economic and family aspects, in order to establish autonomy and co-responsibility of health care.…”
Section: Discussionmentioning
confidence: 99%